1997
DOI: 10.1006/dbio.1997.8546
|View full text |Cite
|
Sign up to set email alerts
|

Delta-1 Is a Regulator of Neurogenesis in the Vertebrate Retina

Abstract: In the retina, cell fate determination is thought to be regulated by a series of local cell-cell interactions. Evidence suggests that retinal precursors utilize Notch-mediated intercellular signaling to regulate their fates. However, the identity of the endogenous ligand and its role in the Notch-signaling pathway is not well understood. We have identified C-Delta-1 as the putative endogenous ligand for Notch, in the developing chick retina. C-Delta-1 is coexpressed spatially and temporally with C-Notch-1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 53 publications
6
64
0
Order By: Relevance
“…We present three independent sets of experiments demonstrating that Notch1 transcription is regulated by SOX2; an unbiased ChIP screen identified Notch1 as a direct target of SOX2 in vivo, DNase footprinting and Luciferase reporter assays showed that SOX2 can bind to Notch1 regulatory regions and regulate the levels of NOTCH1 expression in vitro, and finally, both NOTCH1 and its target Hes-5 are dramatically down-regulated in the retinas of Sox2 hypomorphic mice. Furthermore, ablation of NOTCH1 gives a retinal phenotype similar to that which we describe for Sox2-null mice (i.e., loss of RPCs) (Austin et al 1995;Waid and McLoon 1995;Ahmad et al 1997;Henrique et al 1997;Jadhav et al 2006), and the retinal phenotypes of both Hes-1 and Hes-5 mutant mice are strikingly similar to the phenotype observed in Sox2-hypomorphic mice, in that RPCs aberrantly differentiate and abnormal "rosette-like" structures are present (Ishibashi et al 1994;Tomita et al 1996). The lack of balance between lateral inhibitory signaling by NOTCH1 and proneural gene products results in differentiation of RPCs-a mechanism that may extend to other CNS progenitors.…”
Section: Sox2 and Retinal Progenitor Fate Genes And Development 1197supporting
confidence: 77%
“…We present three independent sets of experiments demonstrating that Notch1 transcription is regulated by SOX2; an unbiased ChIP screen identified Notch1 as a direct target of SOX2 in vivo, DNase footprinting and Luciferase reporter assays showed that SOX2 can bind to Notch1 regulatory regions and regulate the levels of NOTCH1 expression in vitro, and finally, both NOTCH1 and its target Hes-5 are dramatically down-regulated in the retinas of Sox2 hypomorphic mice. Furthermore, ablation of NOTCH1 gives a retinal phenotype similar to that which we describe for Sox2-null mice (i.e., loss of RPCs) (Austin et al 1995;Waid and McLoon 1995;Ahmad et al 1997;Henrique et al 1997;Jadhav et al 2006), and the retinal phenotypes of both Hes-1 and Hes-5 mutant mice are strikingly similar to the phenotype observed in Sox2-hypomorphic mice, in that RPCs aberrantly differentiate and abnormal "rosette-like" structures are present (Ishibashi et al 1994;Tomita et al 1996). The lack of balance between lateral inhibitory signaling by NOTCH1 and proneural gene products results in differentiation of RPCs-a mechanism that may extend to other CNS progenitors.…”
Section: Sox2 and Retinal Progenitor Fate Genes And Development 1197supporting
confidence: 77%
“…The conservation between the fly and vertebrates of numerous aspects of neurogenesis has lead to the speculation that lateral inhibition plays a role in mosaic formation in the vertebrate retina analogous to the role of lateral inhibition during specification and patterning of photoreceptor cells in the Drosophila ommatidia (Cagan and Ready, 1989;Baker et al, 1990;Raymond et al, 1995;Schmitt and Dowling, 1996). In the retina, lateral inhibition plays a role in the specification of early versus late neuronal cell types and has been suggested to have a second role in mosaic organization of the photoreceptor cells through maintenance of radial patterning (Ahmad et al, 1997;Austin et al, 1995;Bernardos, et al, 2005;Waid and McLoon, 1998). Yet, there are conflicting views from mammals on the role of lateral cellular migration and pruning of dendritic processes during formation of the mosaics of interneurons and ganglion cells (Cook and Chalupa, 2000;Eglen et al, 2000;GalliResta, 2002;Lin et al, 2004;Novelli et al, 2004).…”
Section: Mosaic Organizationmentioning
confidence: 99%
“…Besides these diffusible signals, Dll-Notch signaling mediated by cell-cell contacts also limits RGC production. Constitutively activated Notch and elevated Dll signal are shown to decrease RGC generation whereas inhibiting Notch signaling has the opposite effect (Ahmad et al, 1997;Austin et al, 1995;Dorsky et al, 1997;Dorsky et al, 1995;Nelson et al, 2007). Interestingly, both Shh and VEGF signaling activates expression of the DllNotch effector gene Hes1, which has an activity to suppress RGC differentiation (Hashimoto et al, 2006;Sakagami et al, 2009;Wang et al, 2005).…”
Section: Extrinsic Signalingmentioning
confidence: 99%